(Development of Processing of Breakfast Cereals and Rootcrops) - Sutrisniati, Dwi; Junaidi, Lukman (Balai Besar Industri Agro, 2003)
A study to find out the best method in processing of breakfast cereal and root crop has been conducted the materials used were flour from cassava ,corn,soybean,sweet potato,tapioca and seasoning .the proximate analysis and organoleptic test was conducted toevaluate the quality and the acceptance of the product.addition of 2%chocolate powder to the formula can improve the taste and flavor of the product.breakfast cereal and root crops accepted by panelist were products which made from mixed of corn flour cassava (10.10);mixed of sory flour ,sweet potato and tapioca(9:9:2),mixed of corn product which was made from mixed of soy flour has a fat and protein content higher than product which was made from mixed of corn flour.